2000
DOI: 10.1038/sj.jhh.1000982
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in arterial hypertension

Abstract: Systemic arterial pressure is a dynamic and reactive physiological parameter depending on a great many factors. The endothelial cells of the vascular system are responsible for many biochemical reactions maintaining vascular homeostasis and therefore arterial pressure. Arterial hypertension, atherosclerosis and endothelial dysfunction constitute risk factors increasing morbidity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 24 publications
(27 reference statements)
0
18
0
4
Order By: Relevance
“…In a previous study, we had concluded that the pharmacologic effects of metoclopramide + dopamine were carried out by the activation of a-and b-adrenergic receptors rather than by their specific dopaminergic receptors. 23,24 In the present study, we attempted to determine if infusion of metoclopramide + dopamine in healthy and diabetic subjects has any effect on glucose levels and insulin secretion and if there is a correlation between glucose and insulin levels. The results of this study show that infusion with metoclopramide + dopamine produced a significant increase in insulin secretion in healthy subjects and that insulin levels correlated with serum glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we had concluded that the pharmacologic effects of metoclopramide + dopamine were carried out by the activation of a-and b-adrenergic receptors rather than by their specific dopaminergic receptors. 23,24 In the present study, we attempted to determine if infusion of metoclopramide + dopamine in healthy and diabetic subjects has any effect on glucose levels and insulin secretion and if there is a correlation between glucose and insulin levels. The results of this study show that infusion with metoclopramide + dopamine produced a significant increase in insulin secretion in healthy subjects and that insulin levels correlated with serum glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular endothelium is an important component in the control of arterial pressure homeostasis [35]. Endothelial cells release several vasoactive factors, of which NO is perhaps the most important with potent vasodilator action.…”
Section: Arguments For An Important Effect Of Leptin On Endothelial Fmentioning
confidence: 99%
“…1 Similarly, previous data have suggested that there is increased incidence of diabetes during hypertension and about 20% of hypertensive individuals have coexisting diabetes. 2 Increased activity of the renin angiotensin aldosterone system (RAAS) in hypertension and diabetes has been proposed. 3 This upregulation of RAAS results in increased oxidative stress 4 and the formation of reactive oxygen species (ROS), which in turn affect glucose utilization and blood pressure in a setting of hypertension and diabetes.…”
Section: Introductionmentioning
confidence: 99%